Mal-estar na maternidade: (des)encontros entre a mulher e a mãe - Vescovi, Maiara Borlini (2021)
This dissertation aims to analyse, under de point of view of psychoanalysis, the issue of a malaise present in motherhood, whereas the radical disparity between the woman and the mother function, as well as other themes that involve feminine sexuality, present themselves as indispensable investigation points to psychoanalytical theory since the first freudian formulations until the contemporary moment. Although, the very notion of motherhood as feminine essence, as well as the concept of ifancy, are dated constructs that correspond to economical and political requirements proper of modernity, regulated by the medical discourse as a form of biopolitics, as the foucaultian thinking proposes. This contextualization is brought to better delimit the cut subscribed by Freud along with his theory of the unconscious and of infantile exuality, into the hegemonic discourse of his time, where were current the perspectives of motherhood as a natural destine, to which women’s existence would be reduced, because of an biological aptitude for mothering. Though Freud caused a significant crack into the moral and biological discourse about women and sexuality in general, the psychoanalyst yet withholds the point of view that motherhood could be a destine or way out for women due to the undertaking of the femininity, point that caused a countless amount of criticism directed to psychoanalysis, that drives divergences among psychoanalysts to this day. In the face of this, we discussed the specific form of the feminine Oedipus complex, considering its relation to concepts as infantile sexuality, the castration complex and the primacy of the phallus - dimensions that question motherhood as a position longed for the girl as much as it the son would fill the woman’s lack. The complexity of these themes carry Freud into taking feminine sexuality as an unknown point until the very end of his work, and it is reasonable to consider it a riddle to the present days. Thus, we showed how Freud’s points, taken forward by Lacan under the light of strucutural linguistics, allow taking the phallus as a significant and the mother as a position or function exerted into language’s structure. So, it was verifed that motherhood malaise could be related to the relationship between a woman to her own lack, as it responds to phallic logics and to castration by the desire of having a child, which not always resolves femininity issues to a woman.